Mechanical standardisation of mammographic compression using Volpara software. Issue 3 (August 2021) - Serwan, E.; Matthews, D.; Davies, J.; Chau, M.
Abstract: Introduction: Although breast compression is required in routine mammographic practices, current subjective protocols enforcing 'breast tautness' have minimal clinical reproducibility. Whilst objective guidelines of target force (daN) do not consider breast volumes, new measures of pressure (kPa) account for associated variations. The study aims to determine characteristic compressive forces applied at an Australian diagnostic breast clinic, thereby establishing performance success in achieving ideal pressures of 10 kPa. Methods: Parameters of 1972 mammograms were analysed retrospectively from a South Australian diagnostic breast clinic. Raw data were processed using VolparaDensity software; applied compression (force/pressure), breast thickness, breast volume, breast density and average glandular dose estimates were investigated based on breast/paddle contact areas. Results: Distributions of applied average forces is large, yet distributions of applied average pressures are larger; this is internationally comparable. Regarding force-compressions, 98.6% are >5 daN, 16.6% are >10 daN, and 0.0% are >15 daN. Regarding pressure-compressions, 94.5% are >5 kPa, 36.0% are >10 kPa, and 6.3% are >15 kPa. Measures of average breast thickness, volume and density show anatomically consistent trends, with average glandular dose values constant, albeit high. Conclusions: There was a high level of variation of applied compression forces in relation to breast/paddle contact area and an even higher variation in applied pressure. This is comparable with existing literature. Real-time compression pressure standardisation may benefit examination consistency. The relationship between breast volume, contact area, compression force and resultant compression pressure may aid in developing an objective compression protocol for clinical practice. Implications for practice: Practical guidelines may increase the reproducibility of image acquisition, whilst optimizing patient discomfort and additional radiation dose from image repeats. Patient compliance may increase in accordance with perceived advantages of mechanical standardisation, ultimately aiding in the detection of early-stage breast cancer.